2016
DOI: 10.1097/01.prs.0000475762.86580.36
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Stem Cells Promote Peripheral Nerve Regeneration In Vivo without Differentiation into Schwann-Like Lineage

Abstract: Transplanted adipose-derived stem cells did not differentiate into Schwann cells but promoted peripheral nerve regeneration at the injured site. The neuroregenerative ability was comparable to that of Schwann cells. Adipose-derived stem cells at an undifferentiated stage may be used as an alternative cell source for autologous cell therapy for patients with peripheral nerve injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(61 citation statements)
references
References 48 publications
(58 reference statements)
2
57
0
2
Order By: Relevance
“…Since the posterior tibial branch of the sciatic nerve innervates the gastrocnemius muscle, transection of the sciatic nerve results in atrophy of this muscle, while the gastrocnemius muscle regains its mass depending on the amount of axonal reinnervation . The weight of the gastrocnemius muscle indicated that the transplantation of pSCs and dSCs within nerve guide conduits significantly reversed the muscle atrophy (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Since the posterior tibial branch of the sciatic nerve innervates the gastrocnemius muscle, transection of the sciatic nerve results in atrophy of this muscle, while the gastrocnemius muscle regains its mass depending on the amount of axonal reinnervation . The weight of the gastrocnemius muscle indicated that the transplantation of pSCs and dSCs within nerve guide conduits significantly reversed the muscle atrophy (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…This may be due to the number of survived stem cells and the number of differentiated stem cells not meeting the level necessary for therapeutic effect. Another possibility is that 6 th passage hNCSCs may have been less effective in treatment due to changes in its ability to produce growth factors that have been shown to contribute to the positive influence on nerve regeneration in previous studies 3133 . While the mechanism by which hNCSCs lose their efficacy with increasing passage number is largely unknown, studies on MSCs have shown that the growth rate, differentiation ability, and growth factors secretion progressively are decreased with additional passages, possibly due to senescence, spontaneous differentiation, or loss of differentiation potential 3436 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, a range of nerve guidance conduits (NGCs) based on the natural biology of nerve regeneration have been developed and studied in vivo and/or in vitro . In order to acquire ideal repair outcomes, a variety of strategies have been proposed to fabricate NGCs, which range from simple hollow tubes to filled tubes combined with intraluminal fillings, neurotrophic factors, or stem cells . At present, NGCs in hollow tubular structures made by collagen, non‐resorbable hydrogels, or resorbable biopolymers are approved by the Food and Drug Administration (FDA) …”
Section: Introductionmentioning
confidence: 99%